Characterization of Extended-spectrum ?-lactamaseproducing Clinical Isolates of Shigella flexneri (Journal of Health, Population and Nutrition, 2013)
Abstract not available DOI: http://dx.doi.org/10.3329/jhpn.v31i3.16834 J HEALTH POPUL NUTR 2013 Sep; 31(3): 405-408